2002
DOI: 10.1523/jneurosci.22-15-06766.2002
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin ClearanceIn VivoIs Altered to a Greater Extent by Antidepressant-Induced Downregulation of the Serotonin Transporter than by Acute Blockade of this Transporter

Abstract: Serotonin uptake, mediated by the serotonin transporter (SERT), is blocked acutely by antidepressants such as the selective serotonin reuptake inhibitors (SSRIs), but such blockade does not correlate temporally with the onset of therapeutic improvement. Treatment with SSRIs for 21 d induced downregulation of the SERT (Benmansour et al., 1999). The time course of SERT downregulation as well as the time course for its recovery after cessation of treatment with the SSRI sertraline were investigated using tritiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
120
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 38 publications
11
120
3
2
Order By: Relevance
“…Decreased binding of [ 123 I]b-CIT to SERTs after pretreatment with citalopram could be caused by decreased availability of SERTs due to blockage of SERTs by citalopram, by downregulation of the SERT protein, by a change in affinity of [ 123 I]b-CIT for the SERT, or by a combination of these factors. Benmansour et al (2002) showed that marked loss of SERT binding sites due to downregulation occurred in rats only after 10-15 days of SSRI treatment. Therefore, we think it is not likely that SERT downregulation in our subjects occurred within one day after only one dose of citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased binding of [ 123 I]b-CIT to SERTs after pretreatment with citalopram could be caused by decreased availability of SERTs due to blockage of SERTs by citalopram, by downregulation of the SERT protein, by a change in affinity of [ 123 I]b-CIT for the SERT, or by a combination of these factors. Benmansour et al (2002) showed that marked loss of SERT binding sites due to downregulation occurred in rats only after 10-15 days of SSRI treatment. Therefore, we think it is not likely that SERT downregulation in our subjects occurred within one day after only one dose of citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…20 The same infusion period is also required by SSRIs in order to produce a substantial downregulation of SERT. 6,7 Therefore, mice were infused with the SERT-targeting siRNA, a corresponding mmRNA, citalopram or vehicle for 2 weeks into the ventricular system. In situ hybridization analysis revealed a significant downregulation of SERT mRNA in the dorsal as well as median raphe of mice receiving siRNA (Figure 1a).…”
Section: Sirna-induced Specific Knockdown Of Sert Mrna and Protein Inmentioning
confidence: 99%
“…3,4 Emerging studies reveal downregulation of SERT as an adaptive consequence of sustained and high occupancy by chronically administered SSRIs. [5][6][7][8] The downregulation of SERT favorably potentiates the SSRI-mediated increase in the brain serotonergic neurotransmission. [6][7] Further, the lag time required by SSRIs to produce a substantial downregulation of SERT correlates well with the time needed for eliciting a full therapeutic response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 In this patient, the serotonin level was less than the reference range consistent with chronic exposure to sertraline prenatally. However, it is unclear whether the serotonin level or its enhanced neurotransmission with chronic exposure to sertraline contributes to the patient's symptoms.…”
Section: Discussionmentioning
confidence: 66%